Long term changes in serum T4, T3, and TSH in benign thyroid disease - Biersack, H.-J.; Hartmann, F.; Rödel, R.; Reinhardt, M. (Nuklearmedizin - NuclearMedicine, 2004)
Aim: The diagnosis of abnormalities of thyroid function is generally based on the measurement of thyroid hormones and TSH in blood. The recommended reference ranges for serum T4 and T3 as well as TSH are quite wide as the result of large differences in thyroid function tests in healthy persons. It has been proven that the individual variation within an individual is small, compared with the variation between individuals. We investigated long term variations of these parameters in patients with and without benign thyroid diseases. Methods: We performed long term follow-up serum determinations of T3, T4, and TSH in a total of 150 patients for a time period of 3 to 13 years. The majority of patients had been put on L-thyroxine. Values of total T3, total T4, free T4 were measured with an almost unmodified test (RIA) over the years. Results: The lowest relative coefficient of variation (<10%) was observed in the group of patients who had been treated with L-thyroxine only. Even for TSH, relatively low cofficients of variation were observed in this group. In the group of patients who had not received any medication, T3 and T4 showed also a variation of 10%. FT4 and TSH revealed a wider range of variation. Even after radioiodine therapy, T3 and T4 showed only a quite small variation, while TSH demonstrated a wide range with a variation of >30%. Conclusion: Our data demonstrate that there are only narrow variations of serum T4 and T3 within individuals with and without thyroid disorders.
Keywords: Thyroid function; thyroxine; triiodothyronine; TSH